ĐÁNH GIÁ HIỆN TRẠNG VÀ PHÂN VÙNG CẢNH BÁO NGUY CƠ TRƯỢT LỞ ĐẤT TỈNH QUẢNG NAM - Hùng, Phạm Văn (Vietnam Journal of Earth Sciences, 2012)
Review of current status and landslide hazard zonation for the Quang Nam province Based on studies to assess the status and impact factors arising landslide, risk warning zoning map of landslide in Quang Nam has been established. - The province of Quang Nam has 529 sliding blocks, including 262 big sliding blocks and 167 medium blocks. They are distributed into bands such as Tay Giang - Dong Giang, Bac Tra My - Phu Ninh, Nam Giang - Son Phuoc, Hiep Duc - and Nam Giang Duy Xuyen - Dai Loc, with density about 15 - 20 blocks/100 km2. - Landslides occurred due to 10 factors that impact arising, in which slope and rainfall plays a key role, then followed by weathered crust, engineering geology, influenced zones of faults, hydrogeology, fault density, etc.. The map of landslide hazard zonation in Quang Nam province was built by integrated 10 component maps by “analytic hierarchy process” method and spatial analysis in GIS environment. - In the province of Quang Nam, areas with the of high and very high landslide risk distributed in the districts of Tay Giang, Dong Giang, Phuoc Son, Bac Tra My, Tien Phuoc, Duy Xuyen and Phu Ninh; medium landslide risk areas scattered in the districts of Tay Giang, Nam Giang, Nong Son, Nam Tra My, Bac Tra My and Phuoc Son; low and very low risk is distributing in Dien Ban, Thang Binh , Nui Thanh, Hoi An and Tam Ky.